2011
DOI: 10.1590/s1807-59322011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency in Alzheimer's disease, Parkinson's disease, and major depression

Abstract: OBJECTIVE:To compare verbal fluency among Alzheimer's disease, Parkinson's disease, and major depression and to assess the sociodemographic and clinical factors associated with the disease severity.METHODS:Patients from an outpatient university center with a clinical diagnosis of Alzheimer's disease, Parkinson's disease or major depression were studied. Severity was staged using the Hoehn & Yahr scale, the Hamilton Depression scale and the Clinical Dementia Rating for Parkinson's disease, major depression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
(41 reference statements)
1
7
0
1
Order By: Relevance
“…Empirical evidence of impaired word generation performance has been provided for an immense variety of disorders and etiologies, such as dementia (Araujo et al, 2011;Beatty et al, 1997;Rosen, 1980) or mild cognitive impairment (Kleissendorf, Jaecks, & Stenneken, 2009;Nutter-Upham et al, 2008;Östberg, Fernaeus, Hellström, Bogdanovic, & Wahlund, 2005), ischemic or hemorrhagic strokes (Basso et al, 1997;Gaspers et al, 2012;Kim et al, 2011), traumatic brain injury (Drake, Gray, Yoder, Pramuka, & Llewellyn, 2000;Gaspers et al, 2012;Henry & Crawford, 2004), schizophrenia and bipolar disorder (Costafreda et al, 2011;Gourovitch, Goldberg, & Weinberger, 1996;Nicodemus et al, 2013;Paulsen et al, 1996;Rossell, 2006;Sumiyoshi et al, 2014), depression (Araujo et al, 2011;Schmid, Strand, Ardal, Lund, & Hammar, 2011), Parkinson's disease (Piatt, Fields, Paolo, Koller, & Tröster, 1999;Testa et al, 1998), Huntington's chorea (Azambuja, Haddad, Radanovic, Barbaso, & Mansur, 2007;Rosser & Hodges, 1994), multiple sclerosis (Beatty, 2002;Friend et al, 1999;Henry & Beatty, 2006;Thiele, 2013), and autism (Begeer et al, 2013;Inokuchi & Kamio, 2013;Kenworthy et al, 2013). Word generation tasks are also used to specify physiological and pathological conditions of performance across lifespan, which provides information on developmental changes (Henry & Phillips, 2006;Hughes & Bryan, 2002;…”
mentioning
confidence: 99%
“…Empirical evidence of impaired word generation performance has been provided for an immense variety of disorders and etiologies, such as dementia (Araujo et al, 2011;Beatty et al, 1997;Rosen, 1980) or mild cognitive impairment (Kleissendorf, Jaecks, & Stenneken, 2009;Nutter-Upham et al, 2008;Östberg, Fernaeus, Hellström, Bogdanovic, & Wahlund, 2005), ischemic or hemorrhagic strokes (Basso et al, 1997;Gaspers et al, 2012;Kim et al, 2011), traumatic brain injury (Drake, Gray, Yoder, Pramuka, & Llewellyn, 2000;Gaspers et al, 2012;Henry & Crawford, 2004), schizophrenia and bipolar disorder (Costafreda et al, 2011;Gourovitch, Goldberg, & Weinberger, 1996;Nicodemus et al, 2013;Paulsen et al, 1996;Rossell, 2006;Sumiyoshi et al, 2014), depression (Araujo et al, 2011;Schmid, Strand, Ardal, Lund, & Hammar, 2011), Parkinson's disease (Piatt, Fields, Paolo, Koller, & Tröster, 1999;Testa et al, 1998), Huntington's chorea (Azambuja, Haddad, Radanovic, Barbaso, & Mansur, 2007;Rosser & Hodges, 1994), multiple sclerosis (Beatty, 2002;Friend et al, 1999;Henry & Beatty, 2006;Thiele, 2013), and autism (Begeer et al, 2013;Inokuchi & Kamio, 2013;Kenworthy et al, 2013). Word generation tasks are also used to specify physiological and pathological conditions of performance across lifespan, which provides information on developmental changes (Henry & Phillips, 2006;Hughes & Bryan, 2002;…”
mentioning
confidence: 99%
“…In SVF tasks, the words retrieved should belong to a certain category, such as fruits, animals and clothes; whereas animals is the most commonly used category in the literature (Charchat-Fichman, Oliveira, & Silva, 2011). Most Brazilian studies on VF include SVF tasks using the animal category (Araujo et al, 2011;Brucki, Malheiros, Okamoto, & Bertolucci, 1997;Brucki & Rocha, 2004;Caramelli, Carthery-Goulart, Porto, CharchatFichman, & Nitrini, 2007;Lopes et al, 2009;Silva, Yassuda, Guimarães, & Florindo, 2011). There is a small number of studies using fruits (Paula et al, 2010), body parts (Malloy-Diniz et al, 2007), and clothes (Fonseca, Parente, Côté, Ska, & Joanette, 2008;Moraes et al, 2014;Zimmermann, Parente, Joanette, & Fonseca, 2014).…”
mentioning
confidence: 99%
“…However, injury to the orbitofrontal cortex may impair aspects of verbal intelligence such as verbal fluency or performance on the similarity test by different mechanisms (e.g., perseveration). Indeed, some studies have demonstrated an association between the orbitofrontal cortex and the verbal fluency and similarity tests (Araujo et al., ; Lovstad et al., ; Ravnkilde, Videbech, Rosenberg, Gjedde, & Gade, ). On the other hands, the motor series score showed a significant correlation with the gray matter volume of the right orbitofrontal gyrus, whereas the motor series score was not significantly lower in ALS patients than in normal controls.…”
Section: Discussionmentioning
confidence: 99%